An Experimental Investigation of Social Identification on College Student Organ Donor Decisions. Issue 3 (2nd July 2016) - Dillow, Megan R.; Weber, Keith
Abstract : This investigation examined whether persuasive organ donation messages that target individuals' identification with a salient social group will be more effective in encouraging these individuals to become organ donors than will information-only persuasive messages. Participants were randomly assigned to view one of two pro-organ donation messages, both of which included basic information about organ donation (need, number of registered donors, etc.) while one also targeted social identity. Findings indicate that individuals exposed to a social identification message were more likely to click a link that allowed them to officially register as organ donors. These results offer support for the utility of social identification as a health communication campaign strategy for increasing organ donation.